Shine - Hauck, Carley (Ascent Audio, 2021)
The way we do business is changing. Every day, we see new evidence that we've got to move away from the status quo that is burning out workers, enabling greed, and endangering our planet. Yet how do you develop the skills and practical tools to prioritize people, planet, and prosperity? With Shine: Ignite Your Inner Game to Lead Consciously at Work and in the World, Carley Hauck distills the research-based methods and game-changing skills she's brought to corporate settings such as LinkedIn, Pixar, Genentech, Clif Bar, and more. Here you'll learn tools and practices for cultivating the six "inner game skills" for conscious leadership: self-awareness-understand your strengths, blind spots, motivations, and behaviors, and how these impact others; emotional intelligence-learn how to navigate challenging feelings and develop the qualities of empathy and attunement; resilience-how to adapt gracefully to the constant state of change in business and the world; love-lead from the heart, create a caring and collaborative workplace, and build lasting connections based on shared passion and ideals; well-being-self-care techniques to prevent burnout in the workplace and promote sustainability for the planet; and authenticity-embracing the shadow sides of yourself and your workplace through vulnerability, forgiveness, and trust.